Corrosion-resistant fastener and preparation method

By preparing a corrosion-resistant coating composed of a titanium metal layer, a metal oxide layer and an epoxy organic compound layer on the surface of the fastener, the problem of poor corrosion resistance of the fastener in the corrosion environment of the oil and gas field is solved, and the corrosion resistance of the fastener in the oil and gas field is significantly improved. Hardness, bonding and corrosion resistance extend service life.

CN119144938AActive Publication Date: 2024-12-17CHINA NAT PETROLEUM CORP +1

Patent Information

Application Number
CN202310713919.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

The existing fasteners have poor corrosion resistance in corrosive environments in oil and gas fields, resulting in low hardness, poor bonding force, poor friction resistance, insufficient corrosion resistance, and short service life.

Method used

The corrosion-resistant coating is prepared on the surface of the fastener through vapor deposition technology and brushing process. The coating consists of a transition layer, an anticorrosion layer and a sealing layer. The transition layer is a titanium metal layer, the anticorrosion layer is a metal oxide layer, and the sealing layer is Epoxy organic compound layers are used to improve bonding strength, provide corrosion protection and sealing functions respectively.

Benefits of technology

It significantly improves the corrosion resistance and service life of the fastener, solves the problems of low hardness, poor bonding force, poor friction resistance and insufficient corrosion resistance, and improves the protection ability of the fastener.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144938A_ABST
    Figure CN119144938A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion resistant fastener. Comprising a fastener base body. The surface of the fastener base body is coated with a corrosion-resistant coating; the corrosion-resistant coating comprises a transition layer, an anti-corrosion layer and a sealing layer which are sequentially stacked from inside to outside. The corrosion-resistant coating is prepared on the surface of the fastener through a vapor deposition technology and a brushing process. The anti-corrosion coating is sequentially composed of a transition layer, an anti-corrosion layer and a sealing layer, so that the problems that an existing fastener surface protection coating is low in hardness, poor in binding force, poor in friction resistance and insufficient in anti-corrosion performance are effectively solved, the anti-corrosion performance of a fastener is improved, and the service life of the fastener is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oil and gas field tools, and in particular to a corrosion-resistant fastener and a preparation method thereof. Background Art

[0002] Fasteners are commonly used tools in oil and gas fields, primarily made of ordinary carbon steel, high-strength steel, and alloy steel. In various corrosive environments, steel fasteners exhibit poor resistance to corrosion from media such as H2S, CO2, bacteria, water, dissolved oxygen, acids, and alkalis, which can severely impact the normal operation and safety of equipment, electronic and electrical equipment, and industrial engineering structures.

[0003] Currently, the main methods for improving the corrosion resistance of fasteners include zinc infiltration, aluminizing, phosphating, cadmium plating, zinc plating, and chromate treatment. These methods all suffer from low hardness, poor bonding strength, poor friction resistance, and insufficient corrosion resistance. These methods result in a short service life for oil and gas field fasteners, severely limiting their application in corrosive media environments. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention provides a corrosion-resistant fastener and a method for its preparation. Using vapor deposition technology and a brushing process, a corrosion-resistant coating is applied to the fastener surface. This corrosion-resistant coating, sequentially composed of a transition layer, an anti-corrosion layer, and a sealing layer, effectively addresses the low hardness, poor bonding strength, poor friction resistance, and insufficient corrosion resistance of existing fastener surface protective coatings, thereby improving the fastener's corrosion resistance and extending its service life.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A corrosion-resistant fastener includes a fastener base;

[0007] The surface of the fastener substrate is coated with a corrosion-resistant coating; the corrosion-resistant coating comprises a transition layer, an anti-corrosion layer and a sealing layer stacked in sequence from the inside to the outside.

[0008] Preferably, the transition layer is a titanium metal layer, and the thickness of the titanium metal layer is in the range of 1-10 μm.

[0009] Preferably, the anti-corrosion layer is a metal oxide layer, and the thickness of the metal oxide layer is in the range of 2-8 μm.

[0010] Preferably, the metal oxide layer is composed of nano-crystal particles, and the grain size of the metal oxide layer is 100-300 nm.

[0011] Preferably, the sealing layer is an epoxy organic compound layer, and the thickness of the epoxy organic compound layer is in the range of 5-10 μm.

[0012] A method for preparing a corrosion-resistant fastener comprises the following steps:

[0013] Step 1: preparing a transition layer on the surface of the fastener substrate by chemical vapor deposition;

[0014] Step 2, preparing an anti-corrosion layer on the surface of the transition layer by chemical vapor deposition;

[0015] Step 3: Prepare a sealing layer on the surface of the metal oxide layer by spraying.

[0016] Preferably, in step 1, before preparing the transition layer, the surface of the fastener substrate is cleaned by high-energy plasma under vacuum conditions.

[0017] Preferably, in step 1, a titanium metal layer is prepared by chemical vapor deposition to form a transition layer, the deposition temperature of the titanium metal layer is 600-650°C, and the deposition time is 4-10 hours; the titanium metal layer is a titanium carbide layer, a titanium nitride layer and / or a titanium carbonitride layer.

[0018] Preferably, in step 2, a metal oxide layer is prepared by chemical vapor deposition to form a corrosion-resistant layer, the deposition temperature of the metal oxide layer is 1000-1100°C, and the deposition time is 2-5 hours; the metal oxide layer is an aluminum oxide layer, and the aluminum oxide layer is composed of micron crystals with a micron crystal size of 1-3 μm.

[0019] Preferably, in step 3, a spray coating method is used to prepare an epoxy organic compound layer to form a sealing layer, and the thickness of the sealing layer is 5-10 μm.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] The present invention provides a corrosion-resistant fastener, which is coated with a corrosion-resistant coating on its surface. The corrosion-resistant coating consists of a transition layer, an anti-corrosion layer, and a sealing layer. First, a transition layer and an anti-corrosion layer are sequentially formed on the surface of the fastener substrate by a vapor deposition process. Then, a sealing layer is formed on the surface of the anti-corrosion layer by a brushing method, ultimately obtaining a corrosion-resistant coating on the fastener surface. The transition layer can be used to alleviate the mismatch in thermal expansion coefficients between the anti-corrosion layer and the fastener substrate, reduce interfacial stress, and improve the bonding strength between the anti-corrosion layer and the fastener substrate. The anti-corrosion layer is a metal oxide layer with a micron-crystalline structure, which is mainly used to provide corrosion protection, wear resistance, and electrochemical insulation. The sealing layer is an epoxy organic compound layer, which is mainly used to seal the micropores on the surface of the anti-corrosion layer. The sealing layer itself also has good corrosion resistance, thereby further enhancing the corrosion resistance of the fastener. The present invention can effectively solve the problems of low hardness, poor bonding strength, poor friction resistance, and insufficient corrosion resistance existing in existing metal fastener surface protection technologies, significantly improving the corrosion resistance and service life of the fastener surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The figure is a schematic diagram of the structure of a corrosion-resistant coating on the surface of a corrosion-resistant fastener according to the present invention.

[0023] Figure 2 This is a test diagram of the morphology of the anti-corrosion layer on the surface of a corrosion-resistant fastener in Example 1 of the present invention.

[0024] Figure 3 This is a Vickers hardness test chart of a corrosion-resistant fastener in Example 1 of the present invention.

[0025] Figure 4 This is a test diagram of the bonding performance of a corrosion-resistant fastener in Example 1 of the present invention.

[0026] Figure 5 This is a test diagram of the friction resistance performance of a corrosion-resistant fastener in Example 1 of the present invention.

[0027] Figure 6 This is a corrosion resistance test diagram of a corrosion-resistant fastener in Example 1 of the present invention.

[0028] In the accompanying drawings: 1 is the fastener substrate; 2 is the transition layer; 3 is the corrosion-resistant layer; and 4 is the sealing layer. DETAILED DESCRIPTION

[0029] The present invention will be further described in detail below with reference to specific embodiments, which are intended to explain the present invention rather than to limit it.

[0030] A corrosion-resistant fastener of the present invention includes a fastener substrate 1 and a corrosion-resistant coating formed on the surface of the fastener substrate 1.

[0031] The corrosion-resistant coating is composed of a transition layer 2, a corrosion-resistant layer 3 coated on the surface of the transition layer 2, and a sealing layer 4 coated on the surface of the corrosion-resistant layer 3, wherein the transition layer 2 is located between the surface of the fastener substrate 1 and the corrosion-resistant layer 3, and the sealing layer 4 is located on the outer surface of the corrosion-resistant layer 3.

[0032] The present invention provides a method for preparing a corrosion-resistant fastener, wherein the corrosion-resistant coating is prepared by the following steps:

[0033] S1: Clean the fastener surface under vacuum conditions using high-energy plasma. The high-energy plasma is Ar gas plasma, and the cleaning time is 15 to 45 minutes.

[0034] S2. A transition layer 2 is formed on the surface of the fastener by chemical vapor deposition. The transition layer 2 is a titanium metal layer having a thickness of 1-10 μm. The titanium metal layer is deposited at a temperature of 600-650°C for a time of 4-10 hours. The titanium metal layer is a titanium carbide layer, a titanium nitride layer, and / or a titanium carbonitride layer.

[0035] S3. Depositing an anti-corrosion layer 3 on the surface of the titanium metal layer by chemical vapor deposition. The anti-corrosion layer 3 is a metal oxide layer having a thickness of 2-8 μm. The deposition temperature of the metal oxide layer is 1000-1100°C, and the deposition time is 2-5 hours. The metal oxide layer is an aluminum oxide layer. The aluminum oxide layer is composed of micronized crystals with a size of 1-3 μm.

[0036] S4, preparing a sealing layer 4 on the surface of the metal oxide layer by spraying. The sealing layer 4 is an epoxy organic compound layer, and the thickness of the sealing layer is 5-10 μm.

[0037] Example 1

[0038] A corrosion-resistant fastener includes a fastener base 1; in this embodiment, the fastener is a bolt, and the threaded surface of the fastener base 1 is coated with a corrosion-resistant coating. The corrosion-resistant coating is composed, in sequence, of a transition layer 2, a corrosion-resistant layer 3 coated on the surface of the transition layer 2, and a sealing layer 4 coated on the surface of the corrosion-resistant layer 3. The transition layer 2 is located between the surface of the fastener base 1 and the corrosion-resistant layer 3, and the sealing layer 4 is located on the outer surface of the corrosion-resistant layer 3.

[0039] The corrosion-resistant coating is prepared by the following steps:

[0040] S1, put the fastener into the vacuum chamber, and use the vacuum pump to evacuate the vacuum chamber to 10 -4 Pa; then a certain amount of argon is introduced, and a high-frequency pulse voltage is applied to form a high-energy argon plasma to clean the surface of the fasteners. The cleaning time is 35 minutes.

[0041] After cleaning, a certain amount of nitrogen and titanium chloride is introduced into the fastener in step S2 to form a titanium nitride transition layer on the fastener surface by chemical vapor deposition. The deposition temperature is 650°C and the deposition time is 10 hours.

[0042] S3, after the transition layer is prepared, an anti-corrosion layer is prepared on the surface of the transition layer by chemical vapor deposition. The anti-corrosion layer is an aluminum oxide coating, and the anti-corrosion layer is deposited at a temperature of 1050° C. for 5 hours.

[0043] S4, after the anti-corrosion layer is prepared, a sealing layer is prepared on the surface of the anti-corrosion layer by spraying. The sealing layer is a polyimide layer, and the thickness of the polyimide layer sprayed is 10 μm.

[0044] After the sealing layer is prepared on the surface of the fastener, a corrosion-resistant fastener is finally obtained.

[0045] Test results

[0046] Figure 2 This is a test diagram of the surface morphology of the aluminum oxide anti-corrosion layer coated on the surface of a corrosion-resistant fastener of the present invention. Figure 2It is shown in the figure: the alumina grain size in the alumina anti-corrosion layer on the surface of the corrosion-resistant fastener obtained in Example 1 is micron-sized, the grain size is 2 μm, the grains are tightly combined, and the coating density is high.

[0047] Figure 3 This is a hardness test chart of a corrosion-resistant fastener of the present invention. Figure 3 It is shown in Figure 1 that the hardness of the corrosion-resistant fastener obtained in Example 1 is 1600 HV.

[0048] Figure 4 This is a test diagram of the bonding strength of the corrosion-resistant coating on the surface of a corrosion-resistant fastener of the present invention. Figure 4 It is shown in the figure that the bonding strength of the corrosion-resistant coating on the surface of the corrosion-resistant fastener obtained in Example 1 is 65N.

[0049] Figure 5 This is a test diagram of the friction resistance performance of the corrosion-resistant coating on the surface of a corrosion-resistant fastener of the present invention. Figure 5 It is shown in the figure that the friction coefficient of the corrosion-resistant coating on the surface of the corrosion-resistant fastener obtained in Example 1 is 0.2.

[0050] Figure 6 This is a corrosion resistance performance test diagram of a corrosion-resistant fastener of the present invention. Figure 6 It is shown in Figure 1 that the average corrosion rate of the corrosion-resistant fastener obtained in Example 1 is 0.0021 mm / a.

[0051] A corrosion-resistant fastener prepared according to the above method has a corrosion-resistant coating on the surface of the fastener substrate 1 with a hardness of 1200HV-1600HV, a friction coefficient of 0.2-0.5, a bonding force of 40-65N, and an average corrosion rate of 0.0021-0.0085mm / a.

[0052] Example 2

[0053] The method is the same as that of Example 1, except that in step S1 , the high-energy plasma cleaning time is 10 minutes.

[0054] The results show that the grain size of the prepared alumina coating is 220nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1510HV; the friction coefficient is 0.3; the bonding force is 55N; and the average corrosion rate is 0.0045mm / a.

[0055] Example 3

[0056] The method is the same as that of Example 1, except that in step S2, the thickness of the transition layer 2 is 1 μm.

[0057] The results show that the grain size of the prepared alumina anti-corrosion layer is 140nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1200HV; the friction coefficient is 0.5; the bonding force is 40N; and the average corrosion rate is 0.0085mm / a.

[0058] Example 4

[0059] The method is the same as that of Example 1, except that in step S2, the thickness of the transition layer 2 is 5 μm.

[0060] The results show that the grain size of the prepared alumina anti-corrosion layer is 220nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1510HV; the friction coefficient is 0.3; the bonding force is 58N; and the average corrosion rate is 0.0036mm / a.

[0061] Example 5

[0062] The method is the same as that of Example 1, except that in step S3, the thickness of the anti-corrosion layer 3 is 1 μm.

[0063] The results show that the grain size of the prepared alumina anti-corrosion layer is 140nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1400HV; the friction coefficient is 0.4; the bonding force is 48N; and the average corrosion rate is 0.0072mm / a.

[0064] Example 6

[0065] The method is the same as that of Example 1, except that in step S3 , the thickness of the anti-corrosion layer 3 is 4 μm.

[0066] The results show that the grain size of the prepared alumina anti-corrosion layer is 220nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1550HV; the friction coefficient is 0.3; the bonding force is 62N; and the average corrosion rate is 0.0028mm / a.

[0067] Example 7

[0068] The method is the same as that of Example 1, except that in step S3 , the thickness of the sealing layer 4 is 5 μm.

[0069] The results show that the grain size of the prepared alumina anti-corrosion layer is 200nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1570HV; the friction coefficient is 0.3; the bonding force is 62N; and the average corrosion rate is 0.0027mm / a.

[0070] Example 8

[0071] The method is the same as that of Example 1, except that in step S3 , the thickness of the sealing layer 4 is 7 μm.

[0072] The results show that the grain size of the prepared alumina anti-corrosion layer is 210nm; the hardness of the corrosion-resistant coating on the surface of the prepared corrosion-resistant fastener is 1575HV; the friction coefficient is 0.3; the bonding force is 63N; and the average corrosion rate is 0.0025mm / a.

[0073] The present invention provides a corrosion-resistant fastener having a corrosion-resistant coating applied to its surface. The corrosion-resistant coating comprises a three-layer structure consisting of a transition layer, an anti-corrosion layer, and a sealing layer. The transition layer is a titanium metal layer; the anti-corrosion layer is a metal oxide layer; and the sealing layer is an epoxy organic compound layer. The anti-corrosion layer has a micron-crystalline structure. The corrosion-resistant layer exhibits high hardness, strong bonding, resistance to friction and wear, and corrosion resistance. This invention effectively addresses the problem of existing fasteners being susceptible to wear and corrosion under corrosive conditions in oil and gas fields, significantly improving the wear resistance and corrosion resistance of the fastener surface.

[0074] First, a transition layer and an anti-corrosion layer are sequentially prepared on the surface of the fastener substrate through a vapor deposition process, and a sealing layer is prepared on the surface of the anti-corrosion layer by a brushing method, and finally a corrosion-resistant coating is obtained on the surface of the fastener. The transition layer is a titanium metal layer, which is mainly used to alleviate the mismatch in thermal expansion coefficients between the anti-corrosion layer and the fastener substrate, reduce interfacial stress, and improve the bonding strength between the anti-corrosion layer and the fastener substrate; the anti-corrosion layer is a metal oxide layer with a micron-crystalline structure, which is mainly used to provide functions such as corrosion resistance, wear resistance, and electrochemical insulation; the sealing layer is an epoxy organic compound layer, which is mainly used to seal the micropores on the surface of the anti-corrosion layer. At the same time, the sealing layer itself also has good anti-corrosion ability, thereby further enhancing the anti-corrosion performance of the fastener. The present invention can effectively solve the problems of low hardness, poor bonding force, poor friction resistance, insufficient anti-corrosion performance, etc. existing in the existing metal fastener surface protection technology, and significantly improve the corrosion resistance and service life of the fastener surface.

[0075] It should be understood that the protection scope of the present invention is not limited to the specific statements and embodiments in the present invention. All other various specific variations and combinations that can be made by relevant personnel in this field based on the technical features, functional components, etc. disclosed in the present invention without departing from the essence of the present invention are within the protection scope of the present invention. In addition, within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as the embodiments) can be combined with each other to form new or preferred technical solutions, which are also within the protection scope of the present invention. Due to space limitations, they will not be listed here one by one.

Claims

1. A corrosion-resistant fastener, characterized in that: It comprises a fastener base (1); The surface of the fastener substrate (1) is coated with a corrosion-resistant coating; the corrosion-resistant coating comprises a transition layer (2), an anti-corrosion layer (3) and a sealing layer (4) which are stacked in sequence from the inside to the outside.

2. A corrosion-resistant fastener according to claim 1, characterized in that: The transition layer (2) is a titanium metal layer, and the thickness of the titanium metal layer is in the range of 1-10 μm.

3. A corrosion-resistant fastener according to claim 1, characterized in that: The anti-corrosion layer (3) is a metal oxide layer, and the thickness of the metal oxide layer is in the range of 2-8 μm.

4. A corrosion-resistant fastener according to claim 3, characterized in that: The metal oxide layer is composed of nano-crystal particles, and the grain size of the metal oxide layer is 100-300nm.

5. The corrosion-resistant fastener according to claim 1, characterized in that: The sealing layer (4) is an epoxy organic compound layer, and the thickness of the epoxy organic compound layer is in the range of 5-10 μm.

6. A method for preparing a corrosion-resistant fastener, characterized in that: The following steps are included: Step 1, preparing a transition layer (2) on the surface of a fastener substrate (1) by chemical vapor deposition; Step 2, preparing an anti-corrosion layer (3) on the surface of the transition layer (2) by chemical vapor deposition; Step 3: preparing a sealing layer (4) on the surface of the metal oxide layer by spraying.

7. The method for preparing a corrosion-resistant fastener according to claim 6, characterized in that: In step 1, before preparing the transition layer (2), the surface of the fastener substrate (1) is cleaned by high-energy plasma under vacuum conditions.

8. The method for preparing a corrosion-resistant fastener according to claim 6, characterized in that: In step 1, a titanium metal layer is prepared by chemical vapor deposition to form a transition layer (2), the deposition temperature of the titanium metal layer is 600-650° C., and the deposition time is 4-10 hours; the titanium metal layer is a titanium carbide layer, a titanium nitride layer and / or a titanium carbonitride layer.

9. The method for preparing a corrosion-resistant fastener according to claim 6, characterized in that: In step 2, a metal oxide layer is prepared by chemical vapor deposition to form a corrosion-resistant layer (3), the deposition temperature of the metal oxide layer is 1000-1100° C., and the deposition time is 2-5 hours; the metal oxide layer is an aluminum oxide layer, and the aluminum oxide layer is composed of micron crystals with a size of 1-3 μm.

10. The method for preparing a corrosion-resistant fastener according to claim 6, characterized in that: In step 3, a spray coating method is used to prepare an epoxy organic compound layer to form a sealing layer (4), and the thickness of the sealing layer (4) is 5-10 μm.

Citation Information

Patent Citations

  • Multilayer coatings

    CN101732107A

  • Hard alloy coated blade for steel product turning

    CN101879612A

  • Titanium-nitrogen-carbon-aluminum- oxygen nano ceramic coating on low carbon steel surface and preparation method thereof

    CN103496211A

  • Pressure casting mold with double heat-resisting layers on surface and preparation method thereof

    CN108044078A

  • Composite hydrogen retention coating and preparation method thereof

    CN110551984A

Cited By

  • Insulating hard structure suitable for surface of threaded part and preparation method of insulating hard structure

    CN117535622A

  • An insulating hard structure suitable for a threaded member surface and a method of making the same

    CN117535622B